Harmonisation of chemical and biological process in development of a hybrid technology for treatment of recalcitrant metalworking fluid. - Jagadevan, S; Dobson, P; Thompson, I (2011)
Disposal of operationally exhausted metalworking fluids (MWFs) is enormously challenging. In this study the feasibility of employing a sequential Fenton-biological oxidation for the treatment of recalcitrant components of MWF wastewater was investigated. A statistical experimental design was employed to address Fenton reagent (H₂O₂, Fe²⁺) dose optimisation which ensured minimal concentrations of the reagents, thus making the treatment environmentally less toxic to subsequent biological steps and economically viable. This was achieved by employing a five-level-two-variable central composite experimental design. The results demonstrated that Fenton pre-treatment of the MWF effluent greatly improved biodegradability index (BOD₅)/COD increased from 0.160 to 0.538) with a synchronous lowering in the toxicity of the wastewater, making the recalcitrant component more amenable to subsequent biological treatment. An overall decrease of 92% and 86% in chemical oxygen demand (COD) and total organic carbon (TOC), respectively, was achieved by the two-step treatment method developed.